A review on balya action mentioned in Ayurveda - T. S. Mahesh; M. Shreevidya (Journal of Ayurveda and Integrative Medicine, 2014)
Medicinal and dietary substances have been used for various purposes including nutritional from time immemorial. Various activities such as immunomodulator, bulk promoting, nutritional, etc. that enhance strength, immunity, bulk of the body resulted by the use of medicinal or dietary substances are termed in total as Balya in Ayurveda. The term Balya originally stands for all those actions that enhance the "Bala". The word " Bala" refers to the strength and ability of the body or part of the body to cope up with various physical stressors. This term " Bala" refers to various body components and functions as per the science of Ayurveda. Even in the presence of modern scientific knowledge regarding body strength, Ayurveda concepts add varied dimensions to provide detailed explanation of Balya term. The balya action is critically analyzed and discussed in this review.